2021
DOI: 10.1155/2021/6678059
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Artemisia vulgaris Leaves, Originating from Three Different Altitudes of Nepal

Abstract: This study aimed to evaluate and compare the in vivo chronic anti-inflammatory efficacy, from the ethyl acetate and ethanolic extracts of Artemisia vulgaris leaves, grown at three different altitudes in Nepal, by formalin-induced paw edema in Swiss albino mice. Edema was induced on the mice paw by administering 0.2% of formalin injection. Indomethacin was used as a standard drug at the concentration of 5 mg/kg of body weight. Ethyl acetate and ethanolic leaves extract, at the concentration of 200 mg/kg and 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It is listed in the European Pharmacopoeia and is used in traditional Chinese, Hindu, and European medicine. The plant extracts are known for their antioxidant, hepatoprotective, antihyperlipidemic, antimalarial, anti-inflammatory, antispasmolytic, antinociceptive, estrogenic, cytotoxic, antispasmodic and bronchodilator, antibacterial, larvicidal, and antifungal effects (Lee et al, 1998;Gilani et al, 2005;Temraz et al, 2008;Pires et al, 2009;Khan et al, 2009;Erel et al, 2011;Kodippili et al, 2011;Hiremath et al, 2011;Raj Singh et al, 2011;Govindaraj et al, 2013;Afsar et al, 2013;Obistioiu et al, 2014;Saleh et al, 2014;Khan, 2015;El-Tantawy et al, 2015;Oyedemi et al, 2015;Ekiert et al, 2020;Ben Nasr et al, 2020;Pandey et al, 2021). The plants were studied as a potential source of antioxidant phenolic compounds (Melguizo-Melguizo et al, 2020).…”
Section: Lactuca Sativa L (Lettuce)mentioning
confidence: 99%
“…It is listed in the European Pharmacopoeia and is used in traditional Chinese, Hindu, and European medicine. The plant extracts are known for their antioxidant, hepatoprotective, antihyperlipidemic, antimalarial, anti-inflammatory, antispasmolytic, antinociceptive, estrogenic, cytotoxic, antispasmodic and bronchodilator, antibacterial, larvicidal, and antifungal effects (Lee et al, 1998;Gilani et al, 2005;Temraz et al, 2008;Pires et al, 2009;Khan et al, 2009;Erel et al, 2011;Kodippili et al, 2011;Hiremath et al, 2011;Raj Singh et al, 2011;Govindaraj et al, 2013;Afsar et al, 2013;Obistioiu et al, 2014;Saleh et al, 2014;Khan, 2015;El-Tantawy et al, 2015;Oyedemi et al, 2015;Ekiert et al, 2020;Ben Nasr et al, 2020;Pandey et al, 2021). The plants were studied as a potential source of antioxidant phenolic compounds (Melguizo-Melguizo et al, 2020).…”
Section: Lactuca Sativa L (Lettuce)mentioning
confidence: 99%
“…Researchers have confirmed that A. vulgaris exhibits antibacterial, antiseptic, anticancer, and hepatoprotective properties, as well as therapeutic effects in metabolic disorders such as diabetes (18,22). In this regard, recent studies have demonstrated that A. vulgaris can attenuate inflammatory mediators, such as cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) (23,24), increase antioxidant activity by upregulating nuclear factor erythroid 2-related factor 2 (Nrf2) (25), and improve damage levels in an experimental model of colitis.…”
Section: Introductionmentioning
confidence: 99%
“…Te plant production of B. balsamifera has progressively increased in South Asia as a healthy dietary component. Diferent stages of leaf maturation may accumulate varying levels of bioactive chemicals that may be suited for specifc human health purposes [14,15]. To date, there is no ofcial report, but a bioRxiv preprint [16] on the characteristics of EOs extracted from fresh leaves of B. balsamifera at various maturity stages and the extraction efciency of certain volatiles.…”
Section: Introductionmentioning
confidence: 99%